Should haematological inflammatory markers be included as an adjuvant in the differential diagnosis of acute scrotal pathologies?. (18th January 2022) - Yilmaz, Mehmet; Sahin, Yusuf; Hacibey, Ibrahim; Ozkuvanci, Unsal; Suzan, Serhat; Muslumanoglu, Ahmet Yaser
Abstract: The aim of this study was to determine discriminative role of haematological inflammatories between acute scrotal pathologies and malignancies. In addition, it was aimed to search for a predictive marker of testicular survival in the TT group. Medical data of 141 patients with acute scrotal pathology and 63 TTm patients who presented to our clinic between January 2015 and July 2019 were retrospectively reviewed and compared in terms of haematological values and demographic parameters following the inclusion of 92 healthy controls. In the TTm group, NLR was the discriminative parameter with a median of 2.42 (0.25–8.42), whereas discriminative median values of MCV for TT and CRP for EO were 83.65 (56.9–98.16) and 59.5 (2.9–337) respectively. NLR, PLR, MER and RDW values were statistically lower in the control group compared to the patients groups. In TT subgroup analysis, monocyte count, MER and CRP were found to be statistically higher in the orchiectomy group, while multivariate logistic regression analysis performed for testicular viability revealed monocyte count to be the only significant variable (Odds Ratio [95% Confidence Interval] = 0.046 (0.006–0.366), p <0.004). While our study demonstrated both diagnostic and discriminative values of haematological parameters, it also showed that monocyte count could predict testicular salvage in TT patients. However, further prospective studies are required.